If we assume that: $0\le x_1,x_2,\ldots,x_{10}\le\frac{\pi}{2} $ such that:

$$\sin^2 (x_1) +\sin^2 (x_2)+\cdots+\sin^2(x_{10})=1$$ How to prove that:

$$\frac{\cos(x_1) +\cos(x_2) +\cdots+\cos(x_{10})}{\sin(x_1) +\sin(x_2) +\cdots+\sin(x_{10})} \ge 3$$


Since $$ \sin^2(x_1)+\sin^2(x_2)+\dots+\sin^2(x_{10})=1\tag{1} $$ we have $$ \cos^2(x_1)+\cos^2(x_2)+\dots+\cos^2(x_{10})=9\tag{2} $$ Therefore, $$ \frac{\cos^2(x_1)+\cos^2(x_2)+\dots+\cos^2(x_{10})}{\sin^2(x_1)+\sin^2(x_2)+\dots+\sin^2(x_{10})}=9\tag{3} $$ Note that for $0\le x\le\frac\pi2$, we have that $$ \cos(x)-3\sin(x)\ge0\quad\Leftrightarrow\quad\cos(x)+3\sin(x)-\frac6{\sqrt{10}}\le0\tag{4} $$ since they both change signs only at $\arctan(1/3)$:

$\hspace{2cm}$crossing image

Therefore, $(4)$ immediately gives $$ \cos^2(x)-9\,\sin^2(x)\le\frac6{\sqrt{10}}(\cos(x)-3\sin(x))\tag{5} $$ Summing $(5)$ and applying $(3)$, we get $$ \begin{align} 0 &=\sum_{i=1}^{10}\cos^2(x_i)-9\,\sin^2(x_i)\\ &\le\frac6{\sqrt{10}}\sum_{i=1}^{10}\cos(x_i)-3\sin(x_i)\tag{6} \end{align} $$ Inequality $(6)$ yields $$ \frac{\cos(x_1)+\cos(x_2)+\dots+\cos(x_{10})}{\sin(x_1)+\sin(x_2)+\dots+\sin(x_{10})}\ge3\tag{7} $$

  • $\begingroup$ But is ($4$) necessarily true ? i mean when the angle 45 degree or 30 degree. $\endgroup$ – Frank Aug 10 '12 at 22:38
  • $\begingroup$ @MohammedAl-mubark: It is true for all $x\in[0,\frac\pi2]$. Look at the diagram: $\cos(x)-3\,\sin(x)$ is negative precisely when $\cos(x)+3\,\sin(x)-\frac6{\sqrt{10}}$ is positive, and vice-versa. $\endgroup$ – robjohn Aug 10 '12 at 23:32

By Cauchy-Schwarz

$$\left(\sin(x_1) +\sin(x_2) +\cdots+\sin(x_{10})\right)^2 \leq 9 \left( \sin^2(x_1) +\sin^2(x_2) +\cdots+\sin^2(x_{10})\right) =9$$


\begin{equation} \sin(x_1) +\sin(x_2) +\cdots+\sin(x_{10}) \leq 3 \tag1 \end{equation}

Also, since $$0 \leq \cos(x_i) \leq 1$$ we

$$\cos^2(x_i) \leq \cos(x_i)$$


\begin{equation} \cos(x_1) +\cos(x_2) +\cdots+\cos(x_{10}) \geq \cos^2(x_1) +\cos^2(x_2) +\cdots+\cos^2(x_{10})=9 \tag2 \end{equation}

Combining (1) and (2) you get the desired result.

P.S. How can I label equations?

  • $\begingroup$ Af for your P.S., try with the tag \tag{put_here_a_label} at the end of your equations. $\endgroup$ – Salvo Tringali Aug 10 '12 at 15:50
  • 1
    $\begingroup$ Shouldn't it be $(\sin(x_1)+...+\sin(x_{10}))^2\le10(\sin^2(x_1)+...+\sin^2(x_{10}))$ from Cauchy-Schwarz? $\endgroup$ – Christmas Bunny Oct 18 '12 at 0:18

Transform to $y_i=\sin^2 x_i$. Then $\sum_iy_i=1$, and with $\sin x_i=\sqrt{y_i}$ and $\cos x_i=\sqrt{1-y_i}$ the inequality becomes

$$ \sum_i\left(\sqrt{1-y_i}-3\sqrt{y_i}\right)\ge0\;. $$

The left-hand side is $10$ times the average value of $f(y)=\sqrt{1-y}-3\sqrt y$ at the $y_i$. The graph of $f$ has an inflection point at $y=1/\left(1+3^{-2/3}\right)\approx0.675$ and is convex to its left. Either none or one of the $y_i$ can be to its right. If none are, the average value of $f$ is greater or equal to the value at the average, $f(1/10)=0$. If one is, say, $y_i$, then we can bound the average value of the remaining ones by the value at their average, so in this case

$$ \sum_i\left(\sqrt{1-y_i}-3\sqrt{y_i}\right)\ge\sqrt{1-y_1}-3\sqrt{y_1}+9\sqrt{1-(1-y_1)/9}-27\sqrt{(1-y_1)/9}\;. $$

This is non-negative with a single root at $1/10$, so the inequality holds in both cases.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.